Methods of optical absorption reduction in irradiated KDP single crystals containing arsenic ions - Levchenko, A.N. (Functional Materials, 2009)
The processes of disappearance of radiation defects under thermal, laser, and ionizing irradiation annealing in gamma-irradiated potassium dihydrogen phosphate crystals containing arsenic ions have been investigated using electron paramagnetic resonance and optical spectroscopy. It has been found that the disappearance of some types of defect results in optical absorption reduction in crystal. Basing on the spectroscopic measurements, the possibilities, advantages and drawbacks of different crystal treatment methods including the above-mentioned kinds of annealing, have been determined. The optimal conditions of the crystal treatment have been determined. У гамма-опромінених кристалах дигідрофосфату калію, що містять домішкові іони миш'яку, за допомогою електронного парамагнітного резонансу і оптичної спектроскопії досліджено процеси зникнення радіаційних дефектів при термічному, лазерному та радіаційному відпалі. Встановлено, що зникнення визначених типів дефектів приводить до зменшення оптичного поглинання у кристалах. На основі спектроскопічних вимірювань визначено можливості, достоїнства та недоліки різних засобів обробки кристалів, що включають зазначені вище різновиди відпалу. Визначено оптимальні умови обробки кристалів. В гамма-облученных кристаллах дигидрофосфата калия, содержащих примесные ионы мышьяка, с помощью электронного парамагнитного резонанса и оптической спектроскопии исследованы процессы исчезновения радиационных дефектов при термическом, лазерном и радиационном отжиге. Установлено, что исчезновение определенных типов дефектов приводит к уменьшению оптического поглощения в кристаллах. На основе спектроскопических измерений определены возможности, достоинства и недостатки различных способов обработки кристаллов, включающих указанные выше разновидности отжига. Определены оптимальные условия обработки кристаллов.